(untitled) (Arquivos em Odontologia, 2024)
Aim: To develop and validate the Malocclusion Severity Index (MSI), which assesses the presence and severity of malocclusion in primary dentition. Materials and Methods: 294 children aged 3-5 years were examined in 33 occlusal traits by calibrated examiners. Descriptive analysis, and univariate and multivariate linear regressions were performed. A final equation identified the influence of trait on the malocclusion severity of each child (lip coverage x 3) + (crowding x 2) + (diastema x 0.5) + (overbite x 0.5) + (anterior open bite x 1) + (anterior mandibular overjet x 2) + 3 (derived from the constant). The MSI value for each of the participants was calculated. The Kruskal-Wallis test determined the significance between each professional’s assessment and the MSI score (p < 0.05). MSI was categorized as absent, mild, moderate and severe malocclusion. The Mann-Whitney test determined the discriminant validity. Results: Some occlusal traits were independently associated with the perception of the severity of malocclusion by the professional (p < 0.05). Classification of the severity of malocclusion according to the MSI was associated (p < 0.001) with the perception of malocclusion by the professional, which demonstrated the discriminant validity of the instrument. Conclusion: The MSI was effective in discriminating malocclusion in primary dentition by different degrees of severity.